Pemilihan Kepala Daerah Secara Langsung: Garansi Moral dan Demokrasi? - Thalhah, M (Unisia, 2016)
The direct election of the local government will bring some implication in politics, economy and social sphere. Event the direct participation by people to choose their Local Government has some weaknesses according to the circumstance of paternal istic term, nepotisme and primordilism, but we have to aware that this process will bring more participation of the society to the proces of democratitation and people can monitor their own political performance; less possibility for money politics, and more awarness of public accountanbilty.